2013
DOI: 10.1182/blood-2012-10-459883
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib

Abstract: IntroductionProteasome inhibition is highly effective treatment for multiple myeloma (MM), Waldenström macroglobulinemia, low-grade nonHodgkin lymphomas, and primary amyloidosis. 1 Almost 10 years ago, the US Food and Drug Administration (FDA) approved the dipeptidyl boronic acid derivative proteasome inhibitor bortezomib (BTZ) for the treatment of refractory MM and subsequently frontline therapy for MM, thus opening the door to a new era of improved MM therapy. Indeed, disease-free and overall survival for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 74 publications
0
141
0
1
Order By: Relevance
“…Moreover, the combination of the drugs induced apoptosis and cleavage of caspase-3, caspase-9 and PARP more than each of the drugs alone. Carfilzomib is an emerging therapy which was recently approved for the treatment of MM (Kortuem & Stewart, 2013). Previous studies showed that some bortezomib-resistant cell lines (Kuhn et al, 2009) and patients (Vij et al, 2012) were responsive to carfilzomib.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of the drugs induced apoptosis and cleavage of caspase-3, caspase-9 and PARP more than each of the drugs alone. Carfilzomib is an emerging therapy which was recently approved for the treatment of MM (Kortuem & Stewart, 2013). Previous studies showed that some bortezomib-resistant cell lines (Kuhn et al, 2009) and patients (Vij et al, 2012) were responsive to carfilzomib.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The introduction of novel agents, thalidomide, lenalidomide, bortezomib, but also the availability of various others, such as 3rd-generation immunomodulatory drugs (IMiDs; pomalidomide), novel proteasome inhibitors, including carfilzomib, ixazomib and oprozomib, antibodies, such as elotuzumab (target: CS1), daratumumab and SAR650984 (CD38), siltuximab (IL-6), tabalumab (BAFF), denosumab (RANKL), romosozumab (sclerostin), Bruton tyrosine kinase, heat shock protein inhibitors and other innovative phase I/II agents have changed or will alter the therapeutic scenario in several ways. [4][5][6][7] Moreover, cereblon (CRBN) has been identified as a possible biomarker for the assessment of clinical efficacy of IMiDs, although this is still a subject of controversy and CRBN testing needs to be standardized. 8,9 The predictive role of CRBN was assessed in the HOVON/GMMG trial, where higher CRBN expression was associated with better survival and clinical efficacy of thalidomide.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless connectivity is achieved through a Metricom wireless modem or a Lucent WaveLAN adapter. The hardware is described in more detail in [1,2,9,10].…”
Section: A Wearable Agent Systemmentioning
confidence: 99%
“…Among the first systems were several designed at Carnegie-Mellon University [8,12,17]. Similar systems have been built and evaluated at the University of Washington [3,4] and by our own research group [1,2,10]. While [3] is one of the few systems designed for co-located collaboration, it is still a sophisticated, yet traditional videoconference system intended for visual and audio communication.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation